Rangko Village Ecotourism: A Qualitative Review of Potentials and Challenges - Imelda Masni Juniaty Sianipar; I Wayan Koko Suryawan (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2024)
The burgeoning ecotourism industry, aiming for sustainability and minimal environmental impact, has prompted many regions to reevaluate their tourism practices.. This study delves deep into Goa Rangko, a promising destination within Manggarai Barat, Indonesia, by implementing an ecotourism potential framework combined with SWOT analysis. This paper identifies the intrinsic strengths of Goa Rangko, such as its untouched natural beauty, indigenous culture, and governmental initiatives fostering eco-friendliness. It concurrently uncovers weaknesses in the tourism sector, including waste management concerns and the aftermath of the COVID-19 pandemic. The exploration reveals multiple opportunities for sustainable growth, emphasizing unique product promotion, embracing technological advances, and fostering collaborations while accounting for impending threats, such as environmental degradation and competitive destinations. By integrating the ecotourism potential framework with SWOT analysis, this study provides a comprehensive roadmap for Goa Rangko’s tourism sector, highlighting avenues for optimizing tourist experiences and environmental stewardship.